ARTEFAK TERAKOTA BERBENTUK UNIK DARI SITUS GUNUNGWINGKO: TINJAUAN ATAS BENTUK DAN FUNGSI - Goenadi Nitihaminoto (BRIN, 1997)
The uniquely shaped terracotta artifacts from the Gunungwingko Site consist of several shapes that cannot be easily named. The naming is used to identify the shape it belongs to and other names taken from a shape similar to fauna or a certain geomeric form. To find out the function of these artifacts, a contextual comparison is made both with findings of other types in one site, as well as with similar findings on other sites both in Indonesia and outside Indonesia.